2021
DOI: 10.14716/ijtech.v12i1.4281
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention of e-Learning: A Case Study of Distance Learning at a Junior High School in Indonesia due to the COVID-19 Pandemic

Abstract: The spread of COVID-19 caused schools that previously used only a face-to-face system to deliver instruction online from home, a method commonly called e-learning. e-Learning is extremely beneficial in providing cost-effective education irrespective of time and geographical boundaries. Despite the benefit of e-learning, there are many problems associated with its use in Indonesia. Based on the results of research by Indonesian Child Protection Commission (KPAI), the application of e-learning in secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
(42 reference statements)
0
27
0
5
Order By: Relevance
“…Furthermore, several studies that used the unified theory of acceptance and use of integrated technology (UTAUT) observed that the performance expectation strongly influences the behavioral intention to use e-learning [45]. Finally, we can say that e-learning features such as collaborative learning, customization, cost, and, most notably, the performance of e-learning have developed and created a solid positive relationship with behavioral intention [38]. Hence, we hypothesize: H3 (b).…”
Section: E-learning Contents and User Intentionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, several studies that used the unified theory of acceptance and use of integrated technology (UTAUT) observed that the performance expectation strongly influences the behavioral intention to use e-learning [45]. Finally, we can say that e-learning features such as collaborative learning, customization, cost, and, most notably, the performance of e-learning have developed and created a solid positive relationship with behavioral intention [38]. Hence, we hypothesize: H3 (b).…”
Section: E-learning Contents and User Intentionmentioning
confidence: 97%
“…E-learning is a tool for delivering the learning resources via a digital mode, with features such as accessibility and navigation, which empower learners to control the instructional contents. Learners may be involved in learning remotely and without barriers [38]. User satisfaction has a great significance for online learning.…”
Section: E-learning Contents and User Satisfactionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Komite Perlindungan Anak Indonesia (KPAI) menunjukkan 73,2% guru hanya memberikan tugas tanpa adanya interaksi dengan siswa, sehingga siswa merasa tidak menyukai proses pembelajaran jarak jauh. Berdasarkan penelitian tersebut, penerapan elearning di sekolah menengah kurang efektif [10].…”
Section: Pendahuluanunclassified
“…Moreover, there were also publications that have not entirely reached the same theoretical implications. There were conclusions suggesting that some theorized factors had nothing to do with the individual's attitude (Sangeeta & Tandon, 2020;Sukendro, Habibi, Khaeruddin, Indrayana, Syahruddin, Makadada, Hakim, 2020), no connection with their intention (Asvial, Mayangsari, & Yudistriansyah, 2021;Raza, Qazi, Khan, & Salam, 2021;Chayomchai, 2020), and no credibility towards their actual use of technology (Chayomchai, Phonsiri, Junjit, Boongapim, & Suwannapusit, 2020;Sangeeta & Tandon, 2020) during this pandemic.…”
Section: Introductionmentioning
confidence: 99%